MEMPERKUAT POSISI PENDIDIKAN ISLAM DI ERA MEA: (Masyarakat Ekonomi Asean) - Sumaryati (LPPM STAI DARUSSALAM LAMPUNG, 2017)
The free market (MEA) is the economiccolonization undertaken tool developed countries to developing countries. With the free market (MEA) the role of the state in the aplication of tarifs and quotas on good traffic, capital and services will automatically be reduced and even disappear. As a result, countries with more developed industrial conditions will certainly win the market competition. While developing and poor countris simply the object of the marketing industry stronger country. So it can be said that the rich get richer, the poor poorer, but this will not happen if islam can conquer the world, by all means Islamic education devired from this study will not harm each other with each other, and life will be safe, serene, peacefull and prosperous from generation to generation, the more work thatgreets Islamic education. How Islamic education addressing emerging free market (MEA) is still very complex. Islamic education should direct their Islamic sciences in addressing the free market (MEA). There are so many opportunities and challenges and strategies that need to be set up again in the face of the free market.